EFEKTIVITAS GEL EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH YANG DIINFEKSI Staphylococcus aureus - Riski Dwi Utami; Andre Andre; Mahendra Mahendra; Olvaria Misfa (LPPM Universitas Abdurrab, 2025)
In Indonesia, the prevalence of cut wounds is 9.2%. Healing is affected by the wound’s length, depth, and infection, with Staphylococcus aureus being a common infecting bacterium. Starfruit leaf extract, in gel form, offers benefits like ease of application, no residue, and quick drying. This study aimed to assess the effectiveness of starfruit leaf extract gel in healing Staphylococcus aureus-infected cuts in white mice, using a true experimental design with 20 mice divided into four groups: positive control (povidone iodine), negative control (gel base), and two treatment groups with 6% and 12% starfruit leaf extract gels. Bivariate analysis used the one way ANOVA test and continued with the Post Hoc Bonferroni test. The study found the smallest incision length on day 3 was 6% starfruit leaf extract gel group with a mean of 12,505 mm2, while on days 7, 14 and 21 it was group positive control with a mean of 11,867 mm2, 1,367 mm2, 0,000 mm2. The results of the One Way Anova test on days 3, 7, 14 and 21 have a p value < 0.05, meaning there is a significant difference in wound healing between groups. Starfruit leaf extract gel is effective in healing cut wounds in white mice infected with S.aureus. Starfruit leaf extract gel with a concentration of 12% is more effective in healing long cuts infected with S.aureus than a concentration of 6%.